The making of pro-life activists: how social movement mobilization works - Munson, Ziad (Morality and society series, 2008)
Explaining mobilization in the American pro-life movement -- Learning to care -- The mobilization process -- The birth of a movement -- Together but not one : the pro-life movement structure -- United we stand? Tension in the pro-life moral universe -- My life is my argument : religion and the movement -- Becoming an activist : ideas and social movements